Language, abstraction and symbol in Felisberto Hernández’s narrative works (ALPHA. Journal of Arts, Literature and Philosophy, 2019)
By the means of the development of a theoretical model and its furtherapplication to concrete texts, this paper makes its point on the nature of literary language which is understood as the verbalization of an abstract object by means of a “function-symbol” and on the particularities of this nature in Uruguayan writer Felisberto Hernández’s narrative works throughout a revision of the term “metonymy”.
Keywords: Felisberto Hernández; language; abstraction; symbol; metonymy